Bioremediation potential, growth and biomass yield of the green seaweed, Ulva lactuca in an integrated marine aquaculture system at the Red Sea coast of Saudi Arabia at different stocking densities and effluent flow rates. (19th March 2014) - Al‐Hafedh, Yousef S.; Alam, Aftab; Buschmann, Alejandro H.
Abstract Growth, production and biofiltration rates of seaweed, Ulva lactuca were investigated at two stocking densities (3 kg and 6 kg m−2) and two effluent flow rates (5.4 and 10.8 m3 day−1) to optimize an integrated mariculture system at Saudi Red Sea coast. effluents from fish‐rearing tank, stocked with 200 kg fish (Oreochromis spilurus), fed to six seaweed tanks via sedimentation tank. Fish growth (weight gain 1.75 g fish day−1), net production (NP, 10.16 kg m−3) and survival (94.24%) were within acceptable limits. Ulva showed significantly higher (F = 62.62, d.f. 3, 35; P < 0.0001) specific growth rates at lower density compared with higher density and under high flow versus low flow (SGR = 5.78% vs. 2.55% at lower flow and 10.60% vs. 6.26% at higher flow). Biomass yield of Ulva at low‐ and high‐stocking densities (111.11 and 83.2 g wet wt m−2 day−1, respectively) at low flow and (267.44 and 244.19 g wet wt m−2 day−1, respectively) at high flow show that high flow rate and lower density favoured growth. Removal rates of total ammonia nitrogen (TAN) (0.26–0.31 g m−2 day−1) and phosphate phosphorus (0.32–0.41 g m−2 day−1) by U. lactuca were not significantly different (F = 1.9, d.f. 3, 59; P = 0.1394 for TAN and F = 0.29, d.f. 3, 59; P = 0.8324 for phosphates) at both the flow rates and stocking densities. Results show that the effluent flow rate has significant impact over the performance of the seaweed than stocking density.